Linking forests and food production in the REDD+ context - Kissinger, Gabrielle (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Governments implementing REDD+ programmes must address agriculture, which is the primary driver of global forest clearing, to reach REDD+ carbon emission mitigation targets. Current REDD+ readiness activities illustrate there are serious obstacles to creating meaningful cross-sector links able to alter strong economic forces and existing government targets and mandates.